(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This paper delves into the depths of Anton Chekhov's storytelling, analyzing a selection of his most acclaimed short stories to uncover the thematic elements, character development and stylistic techniques that define his work. By examining stories such as "The Lady with the Dog," " The Bet," "The Darling," and "Ward No. 6," this study highlights Chekhov's exploration of human nature, existential dilemmas, societal critiques and the complexities of everyday life. Through a qualitative analysis, the paper demonstrates how Chekhov's economy of language, use of subtext and psychological depth create narratives that remain profoundly relevant and influential. This exploration underscores the enduring significance of Chekhov's contributions to literature and affirms his status as a master of the short story genre.